(untitled) (Current Horticulture, 2024)
Vegetable crops that are not traded widely or economically developed on a large scale are considered underutilized. A few of the vegetables on the list are curry leaf, drumstick, amaranthus, cherry tomato, Chinese cabbage, winged bean, and aquatic veggies etc. Similar to more popular vegetables, these less common vegetables are also vulnerable to a variety of insect and mite attacks over the period of their growth, which can some time cause massive destruction. This chapter describes the list of these insect and acarine pests, their bioecology, host range, damage symptoms, and integrated management techniques in light of the changing climatic conditions.